1990
DOI: 10.1111/j.1399-6576.1990.tb03075.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative emesis after pediatric strabismus surgery: the effect of dixyrazine compared to droperidol

Abstract: Sixty-one children, ASA physical status I, aged 2-14 years, admitted for strabismus surgery were studied. All were premedicated with diazepam and atropin rectally. Anesthesia was induced with thiopental or with halothane on a facemask, and succinylcholine was given to facilitate tracheal intubation. Anesthesia was maintained with halothane and nitrous oxide. Each child was randomly assigned to receive either no antiemetic prophylaxis (control), droperidol 0.075 mg/kg, or dixyrazine 0.25 mg/kg. The drugs were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 15 publications
2
23
1
2
Order By: Relevance
“…The 22-30% incidence of emetic symptoms in this study was low compared with the 41435% reported by other workers (Abramowitz et al 1983;Hardy et al 1986;Broadman et al 1990;Larsson & Johmarker 1990;Horimoto et al 1991). In this study, narcotics the postoperative period.…”
Section: Discussioncontrasting
confidence: 79%
“…The 22-30% incidence of emetic symptoms in this study was low compared with the 41435% reported by other workers (Abramowitz et al 1983;Hardy et al 1986;Broadman et al 1990;Larsson & Johmarker 1990;Horimoto et al 1991). In this study, narcotics the postoperative period.…”
Section: Discussioncontrasting
confidence: 79%
“…We extrapolated variable doses in adults to fixed doses assuming an average bodyweight of 60 kg. In children, only variable doses (5,10,20,40,50,75,200, or 300 µg·kg -1 ), orally or intravenously, were given. Most pediatric trials analysed prevention of vomiting only.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…There were data on 13,352 patients, of whom 5,351 (43%) received droperidol, 3,372 received a placebo or "no treatment", and 4,629 received another anti-emetic intervention. A "no treatment" control was used in fourteen trials, 59,63,65,66,73,75,76,80,83,98,[108][109][110][111] all others used placebos. Data from "no treatment" groups were regarded as placebos.…”
Section: Included and Excluded Trialsmentioning
confidence: 99%
“…2 Sedation was assessed using a four-level Alertness Scale (0 ϭ fully awake, 1 ϭ drowsy, 2 ϭ asleep but easy to arouse, and 3 ϭ asleep and difficult to arouse). 3 Emetic symptoms were defined to be nausea, retching, or vomiting. The time and occurrence of any emetic symptom was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Predischarge emetic symptoms were 50%, 15%, 15%, and 5% in Groups 1, 2, 3, and 4, respectively (p Ͻ 0.009). Peak emetic symptoms were observed after discharge: 75%, 40%, 35%, and 15% in Groups 1,2,3,and 4, respectively (p Ͻ 0.003). Convalescence times, including awakening, extubation, recovery, and hospitalization, were unaffected by increasing droperidol dose.…”
mentioning
confidence: 89%